Sistem Kehadiran Elektronik Bersepadu Untuk Sekolah Kebangsaan Peserai - Bakar, Nur Adilah; Salamat, Mohamad Aizi (Applied Information Technology And Computer Science, 2022)
Integrated Electronic Attandance System for Sekolah Kebangsaan Peserai is a student attendance system that uses a web -based Qr Code. Similarly, attendance is taken manually using a process as students have to fill in the attendance name via Whatsapp, Telegram or Google Form and the teacher will mark the attendance name that has been filled in by the student one by one. This system will facilitate teachers in the process of taking attendance to be more effective and even all the problems encountered can be overcome effectively. The system is also developed using Agile methodology which involves five processes namely planning phase, analysis phase, design phase, development phase, testing phase, and feedback. This approach is an alternative for teachers who want to make the process of taking student attendance more efficient. Thus, this project will achieve goals including saving teachers time in handling student attendance and preventing false attendance records from occurring. The system can generate reports and graphs stored in a student attendance database